ANALISIS PRODUKSI LISTRIK DI PEMBANGKIT LISTRIK TENAGA MINIHIDRO (PLTM) - Arif Rahman Hafiz; Agus Nuramal; Nurul Iman Supardi (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2022)
Mini-hydro Power Plant (PLTM) is one of the hydroelectric power plants of choice where PLTM utilizes water energy which has a flow capacity that is not too large. The Padang Guci PLTM with a capacity of 3x2 MW is located in the Air Padang Guci River, under the auspices of PT. Sahung Brantas Energi in collaboration with the Kaur district government to improve electrical energy services to the community. The electrical energy produced by the Padang Guci PLTM is highly dependent on the flow capacity of the Padang Guci river. The data collection process is carried out to retrieve data about voltage, current, time, and electricity production generated by the generator. The electricity produced by the generator can be seen in kWh in the control room. Data on electricity production, current, and voltage on the kWh meter are then inputted into the computer in the operator's room. Every half hour the data is recorded in the table, the daily data table will be entered into excel and will be inputted into the monthly data. Total electricity production during July 2021 is 1,444,252 kWh and the average daily electricity production is 46,588.77 kWh. With the highest daily electricity production, which is 77,644 kWh, the main cause of the increase in electricity production is due to rain which causes flooding in the river flow so that the turbine operates optimally, because the flow rate required is sufficient to power the three turbines to a maximum of 2 MW. Then for the lowest electricity production, which is 5,124 kWh, due to trips and less flow rate.